Popular political attitudes in Samoa: Findings of the Pacific Attitudes Survey. Issue 3 (18th September 2022) - Leach, Michael; Barbara, Julien; Chan Mow, Ioana; Vaai, Sina; Mudaliar, Christopher; Amosa, Patila; Mataia, Louise; Tauaa, Susana; Imo, Taema; Heem, Vernetta
Abstract: Popular political attitudes surveys have been conducted globally for several decades, but the Pacific region remains an exception. This paper presents the findings of the first Pacific Attitudes Survey (PAS), conducted in Samoa from December 2020‐January 2021. Drawing on a nationally representative sample of Samoans of voting‐age (n = 1319) the PAS gauges the attitudes of ordinary Samoans to their democracy, levels of popular trust in institutions, attitudes towards the role of government,  and to women's participation in politics. Findings reveal high levels of support for democracy and trust in democratic institutions. At the same time, popular political attitudes highlight a distinct model of Samoan democracy, in which respect for modern democratic norms is tempered and entwined with deeper traditions of Samoan community and identity.